ANALYSIS OF BATS MARKETING CHANELS - Sampow, Stevandi (Jambura Journal of Animal Science, 2024)
Bats are the mammals with the most species after rodents (Rodentia). This study aims to know the marketing channels of bats in Olibu Village, Paguyaman Pantai District, Boalemo Regency. This study uses a survey method using a questionnaire. Data analysis uses data reduction techniques, data display, and conclusions drawing. The bat catching process is influenced by several things, including; 1) use of lifting equipment (mist net), 2) number of catches and frequency of catches, 3) number of catchers, 4) bat containers/quarantine, 5) bat sorting, 6) bat marketing. Marketing channel I is a marketing channel that does not use intermediary traders, where catchers directly receive payment for bats directly from consumers. Marketing channel II, the percentage of price received by the catcher is 75%. This is due to the difference in price at the catcher and consumer levels. The price at the catcher level is IDR 15,000 and the price at the consumer level is IDR 20,000, so the catcher's share on this marketing channel is 75%. Marketing channel III, the percentage of price received by the catcher is 62.5%. This is due to the difference in price at the catcher and consumer levels. The price at the catcher level is IDR 15,000 and the price at the consumer level is IDR 24,000, so the catcher's share on this marketing channel is 62.5%. The most efficient marketing channel is marketing channel I compared to channels II and III